تحسين وثوقية وفعالية الصمامات مستقيمة التدفق باستخدام الطرق الرقمية - اسبر, منى (Latakia University Journal -Engineering Sciences Series, 2017)
تصف هذه الدراسة تحسين وثوقية وفعالية الصمامات مستقيمة التدفق المستخدمة في الضواغط المكبسية، وذلك عن طريق نمذجة تدفق الغاز وحركة صفيحة الصمام. يُحدد هذا النموذج توزع ضغط الغاز وتشوهات صفيحة الصمام على أنها صفيحة مرنة.تمَّ اختبار هذه النمذجة عن طريق قياسات تدفق الغاز الستاتيكي في الصمام بالإضافة إلى القياسات الديناميكية لنهاية حركة صفيحة الصمام في الضاغط الاختباري حيث تمت المقارنة بين النتائج الرقمية والنتائج التجريبية المقاسة.This study describes the improvement of the reliability and effectiveness of the straight flow used in piston compressors, valves, and by modeling the flow of gas and the movement of plate valve. This model distributes the gas pressure and distortions plate valve as a flexible plate to be determined.This modeling test gas flow through the valve in the static measurements in addition to dynamic measurements of the end plate valve movement in the compressor has checksum where the comparison between numerical results and experimental results measured.